COMMUNICATION OF PROFESSIONAL CAREGIVERS IN ESTABLISHING INTERPROFESSIONAL COLLABORATION AT MEURAXA HOSPITAL, BANDA ACEH - Sri Wahyuni; Nova Dian Lestari; Dedy Syahrizal (Indonesian Journal of Health Administration, 2021)
Background: Interprofessional collaboration for patient care is integrated cooperation between health workers in ensuring optimally consecutive patient care. Interprofessional decisions should be made in two ways between professional caregivers.Aims: This study aimed to analyze communication between professional caregivers in establishing interprofessional collaboration at Meuraxa District General Hospital in Banda Aceh.Method: This study was qualitative research and used a phenomenological approach. In-depth interviews and FGD were conducted with professional caregivers consisting of doctors in charge, nurses, pharmacists, and dietitians. All of the in-depth interviews and FGD were recorded and transcribed. Data obtained were analyzed thematically.Results: Communication between professional caregivers in establishing interprofessional collaboration at the hospital had not been well-performed. Overall, they had not optimally utilized integrated patient progress records as they focused on taking care of their patients individually. They also lacked literacy about the information in the records. Inadequate time in serving patients and the insufficient number of human resources were presumed to hamper interprofessional communication.Conclusion: Promoting interprofessional collaboration and effective communication regularly is required by the hospital management. They also need to evaluate the sufficiency of human resources, especially pharmacist positions. Besides, they can formulate supervision and evaluation systems of interprofessional communication between professional caregivers. Keywords : communication, integrated patient progress record, interprofessional collaboration, professional caregivers